Description of the previously unknown advertisement call and tadpole of the Colombian endemic glassfrog Centrolene savagei (Anura: Centrolenidae) - Díaz-Gutiérrez, Natalia; Vargas-Salinas, Fernando; Rivera-Correa, Mauricio; Rojas-Morales, Julián Andrés; Escobar-Lasso, Sergio; Velasco, Julián A.; Gutiérrez-Cárdenas, Paul David Alfonso; Amézquita, Adolfo (Zootaxa, 2013)
Glassfrogs (family Centrolenidae) are a charismatic group that currently contains about 149 species biogeographically restricted to the Neotropics (Frost 2013). The advertisement call and tadpole has been described for less than 25% glassfrog species, 32 and 35 species respectively (e.g. Márquez et al. 1996; Ospina-Sarria et al. 2011). Centrolene savagei (Ruiz-Carranza & Lynch 1991; Fig. 1) is a species of relatively small size frogs (mean snout-vent length, SVL, females: 23.6 mm, males: 21.1 mm) occurring in both the Western and Central Andes (Cordillera Occidental and Cordillera Central) of Colombia, between 1400–2410 m a.s.l. (Ruiz-Carranza & Lynch 1991; Rojas-Morales et al. 2011). Although there is some information regarding egg attendance and natural history of C. savagei (Vargas-Salinas et al. 2007), neither the advertisement call or the larval morphology have been described.